2015
DOI: 10.1002/cssc.201501110
|View full text |Cite
|
Sign up to set email alerts
|

Solid Polymer Electrolytes Based on Functionalized Tannic Acids from Natural Resources for All‐Solid‐State Lithium‐Ion Batteries

Abstract: Solid polymer electrolytes (SPEs) for all-solid-state lithium-ion batteries are prepared by simple one-pot polymerization induced by ultraviolet (UV) light using poly(ethylene glycol) methyl ether methacrylate (PEGMA) as an ion-conducting monomeric unit and tannic acid (TA)-based crosslinking agent and plasticizer. The crosslinking agent and plasticizer based on natural resources are obtained from the reaction of TA with glycidyl methacrylate and glycidyl poly(ethylene glycol), respectively. Dimensionally stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
(82 reference statements)
2
26
0
Order By: Relevance
“…Cross‐linking of LPG by heat treatment during drying of the cathode was confirmed by FT‐IR spectroscopy and solubility testing in THF (Figure S8). Furthermore, the surface of the cathode was further coated with PPEGMA linear polymer synthesized by free radical polymerization (see Figure S9 for synthetic scheme and 1 H NMR spectroscopy, and GPC results for PPEGMA) by a direct solution casting method to soak the porous inner space of the cathode, thereby readily forming an ion‐conductive pathway for the facile ion conduction . Prior to the evaluation of cycling performance, the electrochemical stability of LPGP10 was verified by cyclic voltammetry (Figure S10).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Cross‐linking of LPG by heat treatment during drying of the cathode was confirmed by FT‐IR spectroscopy and solubility testing in THF (Figure S8). Furthermore, the surface of the cathode was further coated with PPEGMA linear polymer synthesized by free radical polymerization (see Figure S9 for synthetic scheme and 1 H NMR spectroscopy, and GPC results for PPEGMA) by a direct solution casting method to soak the porous inner space of the cathode, thereby readily forming an ion‐conductive pathway for the facile ion conduction . Prior to the evaluation of cycling performance, the electrochemical stability of LPGP10 was verified by cyclic voltammetry (Figure S10).…”
Section: Resultssupporting
confidence: 79%
“…The long‐term cycling performance of the cells with LPGP10 and Celgard was tested at a rate of 0.1 C at 60 °C. Since LPGP10 has relatively low ionic conductivity, the cell performance was tested at a low current density of 0.1 C, as for the other SPE cell systems . Higher discharge capacity values were obtained during 50 cycles in the case of the cell with LPGP10 compared to that of the cell with Celgard, and outstanding capacity retention after 50 cycles was observed with LPGP10 (98 %), presumably due to the formation of stable SEI layer as well as the suppression of lithium dendrite growth .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, several approaches have been developed to increase the amorphous content in the PEO-based electrolytes for achieving higher Li + conductivities at room temperature [9]. J. C. Lee [10] developed a new SPE by polymerization induced by ultraviolet light using poly(ethylene glycol) methyl ether methacrylate (PEGMA) as an ion-conducting monomeric unit and tannic acid (TA)-based crosslinking agent and plasticizer. The all-solid-state battery using this new SPE at 60 C exhibited good capacity retention ($75%) after 50 cycles with a charge-discharge rate of 0.1C.…”
Section: Introductionmentioning
confidence: 99%
“…Flat surfaces without any wrinkles and pores were observed from the surface SEM images of the SPEs (Figure S9), indicating that macroscopic phase separation or aggregation did not occur in this system . When the crosslinked SPEs were prepared using methacrylated tannic acid and poly(ethylene glycol) methyl ether methacrylate (PEGMA) according to our previous study, wrinkles and pores were observed on the surface of the SPEs caused by the phase separation of electrolyte components, because they are not miscible . This time, the crosslinked SPEs prepared using polysiloxane‐based BPT and terpene‐based crosslinker do not show any phase separation behavior, because relatively nonpolar limonene or geraniol can be mixed well in the nonpolar BPT domains.…”
Section: Resultsmentioning
confidence: 85%